Effect of COVID-19 outbreak on the treatment time of patients with acute ST-segment elevation myocardial infarction - Fu, Xin-yan (Am J Emerg Med, 2021)
OBJECTIVE: To explore the effect of COVID-19 outbreak on the treatment time of patients with ST-segment elevation myocardial infarction (STEMI) in Hangzhou, China. METHODS: We retrospectively reviewed the data of STEMI patients admitted to the Hangzhou Chest Pain Center (CPC) during a COVID-19 epidemic period in 2020 (24 cases) and the same period in 2019 (29 cases). General characteristics of the patients were recorded, analyzed, and compared. Moreover, we compared the groups for the time from symptom onset to the first medical contact (SO-to-FMC), time from first medical contact to balloon expansion (FMC-to-B), time from hospital door entry to first balloon expansion (D-to-B), and catheter room activation time. The groups were also compared for postoperative cardiac color Doppler ultrasonographic left ventricular ejection fraction (LVEF),the incidence of major adverse cardiovascular and cerebrovascular events (MACCE),Kaplan-Meier survival curves during the 28 days after the operation. RESULTS: The times of SO-to-FMC, D-to-B, and catheter room activation in the 2020 group were significantly longer than those in the 2019 group (P < 0.05). The cumulative mortality after the surgery in the 2020 group was significantly higher than the 2019 group (P < 0.05). CONCLUSION: The pre-hospital and in-hospital treatment times of STEMI patients during the COVID-19 epidemic were longer than those before the epidemic. Cumulative mortality was showed in Kaplan-Meier survival curves after the surgery in the 2020 group was significantly different higher than the 2019 group during the 28 days.The diagnosis and treatment process of STEMI patients during an epidemic should be optimized to improve their prognosis.